Safety and tolerability of lacosamide monotherapy in the elderly: A subgroup analysis from lacosamide trials in diabetic neuropathic pain. Issue 4 (11th September 2017) - Bainbridge, Jacquelyn; De Backer, Marc; Eckhardt, Klaus; Tennigkeit, Frank; Bongardt, Sabine; Sen, David; Werhahn, Konrad J.; Shaibani, Aziz; Faught, Edward
Summary: Objective: To assess the safety profile of lacosamide monotherapy in elderly (≥65 years) subjects with diabetic neuropathic pain (DNP). Methods: Of 1, 863 DNP subjects in double‐blind, randomized, placebo‐controlled trials of lacosamide monotherapy (NCT00861445, NCT00235469, NCT00238524, NCT00135109, NCT00350103), 502 were elderly. Safety data from elderly subjects were compared with that of younger subjects (<65 years) within these DNP trials. It should be noted that lacosamide is approved for the treatment of focal (partial‐onset) seizures; it is not approved/recommended for the treatment of DNP. Results: Overall, cardiovascular diseases were prevalent in the DNP population, as was the use of cardiac, blood pressure, diabetes, and cholesterol‐lowering medications among both young and elderly subjects. The most frequently reported adverse events (AEs) for lacosamide monotherapy (200, 400, and 600 mg/day combined) in elderly versus younger subjects were dizziness (16.2% vs. 13.2%), nausea (10.0% vs. 9.4%), and headache (8.0% vs. 8.7%). Incidences of cardiac disorder AEs were higher in elderly versus younger subjects receiving placebo (6.2% vs. 3.9%), lacosamide 200 (4.8% vs. 3.3%), lacosamide 400 (7.0% vs. 4.1%), and lacosamide 600 mg/day (7.7% vs. 4.0%). Discontinuation rates because of any AE in the elderly versus younger subjects were similar for placebo (8.8% vs. 7.0%) and lacosamide 200 mg/day (9.6% vs. 11.9%) and higher for lacosamide 400 (25.1% vs. 10.8%) and lacosamide 600 mg/day (52.7% vs. 28.3%). Significance: Lacosamide monotherapy was well tolerated in elderly subjects with DNP, with an overall AE profile consistent with that reported in epilepsy trials.